THE introvert's EDGE TO NETWORKING ; Work the Room, Leverage Social Media, Develop Powerful Connections - Pollard, Matthew; Lewis, Derek (New York : HarperCollins Leadership, an imprint of HarperCollins Focus LLC, 2021)
"Introverts across the world have been sold a lie: One of the biggest myths that plagues the business world today is that our ability to network depends on having the "gift of gab". This is nonsense. You don't have to be outgoing to be successful at networking. You don't have to become a relentless self-promoter. In fact, you don't have to act like an extrovert at all. The truth is, introverts make the best networkers...when armed with a plan that lets them be their authentic selves."--Amazon.
t Channeling your superpower -- t Our difference defines us -- t The step everyone forgets -- The feedback factory -- The digital frontier.
Includes index.
Keywords: Introverts; Business networks; Success in business